Stylistic And Pragmatic Features Of Phraseological Units In The Works Of Oscar Wilde And Their Preservation In Translation (Texas Journal of Philology, Culture and History, 2024)
The article analyses the stylistic and pragmatic functions of phraseological units in the novel “The picture of Dorian Gray” by the famous English writer Oscar Wilde. This article considers the classification of phraseological units used in the novel in English and their preservation in translation text into Uzbek. This novel contains fragments of English culture and art of that time